Pengaruh Gaya Hidup dan Kemudahan Bertransaksi terhadap Keputusan Menggunakan QRIS pada Mahasiswa Manajemen UKI Toraja - Vivi Gloria Anggreini; Yohanis Lotong Ta’dung (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to analyze the influence of lifestyle and transaction convenience on the decision of Management students at the Indonesian Christian University (UKI) Toraja to use QRIS. The research employed a quantitative approach with a sample of 82 students from the 2022 cohort, selected using purposive sampling. The collected data were analyzed using multiple linear regression to examine the effect of the independent variables on the decision to use QRIS. The results indicate that, partially, lifestyle has a positive and significant effect on the decision to use QRIS. The same applies to transaction convenience, which significantly encourages students to adopt this digital payment system. Simultaneously, both variables were also found to have a significant influence on the decision to use QRIS, with a coefficient of determination of 0.504. This indicates that 50.4% of the variation in students’ decisions to use QRIS can be explained by lifestyle and transaction convenience, while the remaining portion is influenced by other factors beyond this study. In conclusion, the adoption of QRIS by students is driven by a lifestyle that is adaptive to new technology and reinforced by their perception of the efficiency and practicality offered by this digital payment system. This study provides valuable insights for developing strategies to educate and promote QRIS among students.